2019
DOI: 10.1080/09540105.2019.1594704
|View full text |Cite
|
Sign up to set email alerts
|

Butyricicoccus plays a key role in mediating the antagonism between probiotic and antibiotic on food allergy

Abstract: Food allergy is a severe food safety problem worldwide. Probiotics are effective in alleviating food allergy whereas antibiotics may exacerbate allergenic responses, but the knowledge on the interplay between them during food allergy is limited. In the present study, we investigate the activity of probiotic strain Lactobacillus casei (Lc) and antibiotic cocktail (Abx) on in a food allergy mouse model. The results showed that Lc relieved allergenic symptom and changed allergen-specific antibodies isotypes. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Lactic acid bacteria such as Lactobacillus and Bifidobacterium have a long association with health benefits, so the increased relative abundance of Lactobacillus after the red-fleshed apple intervention is a notable finding. Butyricicoccus , a butyrate producer, was another bacterium associated with health benefits [ 52 , 53 , 54 ] that was increased in response to consumption of the red-fleshed apple. However, there were other changes to the faecal microbial community after consumption of the red-fleshed apples that could be considered negative or detrimental; Roseburia , a prominent butyrate producer [ 48 , 55 , 56 ] was decreased, and Sutterella , a Proteobacteria often associated with disease conditions [ 57 , 58 ], was increased after the red-fleshed apple intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acid bacteria such as Lactobacillus and Bifidobacterium have a long association with health benefits, so the increased relative abundance of Lactobacillus after the red-fleshed apple intervention is a notable finding. Butyricicoccus , a butyrate producer, was another bacterium associated with health benefits [ 52 , 53 , 54 ] that was increased in response to consumption of the red-fleshed apple. However, there were other changes to the faecal microbial community after consumption of the red-fleshed apples that could be considered negative or detrimental; Roseburia , a prominent butyrate producer [ 48 , 55 , 56 ] was decreased, and Sutterella , a Proteobacteria often associated with disease conditions [ 57 , 58 ], was increased after the red-fleshed apple intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our previous study showed that LcZ regulates intestinal microbiota homeostasis to regulate immune system. [ 63 ] Previous studies also demonstrated that specific bacterial species from microbiota can promote the expression of ROR‐γt in Treg in a MyD88‐depenent way. [ 64 ] Considering that Myd88 is a crucial regulator in NF‐κB pathway, whether LcZ activity is also mediated by MyD88/ROR‐γt/Treg signaling is an interesting question.…”
Section: Discussionmentioning
confidence: 99%
“…Butyricicoccus was found to be negatively correlated with a number of clinical indicators by Zeng et al [63] and, unsurprisingly, was also discovered as a mediator of probiotic and antibiotic administration aimed at reducing food allergies in mice [58] .…”
Section: Discussionmentioning
confidence: 99%